The Ophthalmic Laser Handbook - Lighthizer, Nathan (Wolters Kluwer Health, 2021)
"As new laser technology continues to emerge in the eye care field, there is a need for an up-to-date, comprehensive resource for eye care providers who are learning or currently performing these laser procedures. Edited by Lars Freisberg, Nate Lighthizer, Leonid Skorin, Jr., Karl Stonecipher, and Aaron Zimmerman, The Ophthalmic Laser Handbook is a practical, clinical guide that covers everything from indications and procedural techniques to contraindications and potential adverse events. This all-in-one reference, including over 45 videos of laser procedures in the e-version, is designed for all eye care providers-from those performing the procedures to those co-managing pre- and post-operative visits. , Reviews all current lasers used across all regions of the eye. Features complete coverage of each procedure, including background, indications, contraindications, informed consent, pre- and post-operative considerations, complications, efficacy, billing/coding, and more. Presents bulleted lists of key information in every chapter for quick reference. Includes videos of all major laser procedures being performed by the author team of renowned ophthalmologists and optometrists. Provides a portable, easy-to-use resource for everyday clinical use and for the professional development of students, residents, and practitioners. , Enrich Your eBook Reading Experience Read directly on your preferred device(s), such as computer, tablet, or smartphone. Easily convert to audiobook, powering your content with natural language text-to-speech. , "--